Coaching as a tool of change - Moyes, Barbara (Henry Stewart Talks, 2009)
What is coaching, and how do you coach?, A key coaching model explained, The special issues facing public sector leaders, How coaching can help them, Why it is successful
Reviewed at 2020/05/31